HUBUNGAN DUKUNGAN SUAMI DENGAN PERILAKU WANITA HAMIL DI USIA KURANG DARI 20 TAHUN DALAM MENGHADAPIKEHAMILAN DI PUSKESMAS TLOGOSARI KULON KOTA SEMARANG - Purwinasih -; Nuke Devi Indrawati2; Program Studi D III Kebidanan Fakultas I dan Kesehatan Universitas Muhammad (Jurnal Ilmiah Kesehatan Keperawatan, 2014)
Health reproduction was one of important topic in health department to reach condition of health reproduction wich healthly time for a woman pregnant and birthing between 20 years old until 25 years old. When the pregnant mothers age 20 years old hook on to husband were being her couple. Husband supported were a big share to determine health status of pregnant mothers. This aim of this study is  to know correlation between husband supported with  pregnant mothers behaviour with age 20 years old during of pregnancy in Public Health Center Tlogosari Kulon Semarang. This study  Used correlations analitic research by cross sectional approaching method. Popultion this research werw woman pregant who examine at BKIA Public Health Center Tlogosari Kulon by the sample saturated tehnic thirty two respondents. Data analyze univariate and bivariate. Hypothesis was analyze test by Chi-Square test α = 0,05. This research gotten sixteen respondents (50%) supported husband with pregnancy and most of seventeen responden (53,1%) the age of woman pregnant less than twenty years old were negative behavior. Analyze test by Chi-Square test ρ = 0,005 < α = 0,05 it was showed that there is significant correlation between husband supported with  pregnant mothers behaviour wth age 20 years old during of pregnancy. Keywords :Supported husband, behaviour, pregnancy, young age